Evaluation of biomechanical properties and biocompatibility: are partially absorbable cords eligible for anterior cruciate ligament reconstruction? - Xu, Fei; Li, Yanlin; Yu, Yang; Wang, Guoliang; Cai, Guofeng (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Independent augmentation technology based on reinforcing devices has been reported to signifi-cantly reduce the elongation behavior of graft and improve knee stability after anterior cruciate ligament reconstruction (ACLR). Using biodegradable devices could reduce the risk of severe inflammatory reactions due to particle accumulation from foreign bodies. Given the limitations of the mechanical properties of biodegradable materials, partially biodegradable composite devices may offer a compromise strategy. Methods: Three types of partially absorbable core-sheath sutures, including low-absorbable cord (LA-C), medium-absorbable cord (MA-C) and high-absorbable cord (HA-C), were braided using unabsorbable ultra-high molecular weight polyethylene (UHMWPE) yarn and absorbable polydioxanone (PDO) monofil-ament bundle based on the desired configuration. The feasibility of these partially absorbable cords were verified by biomechanical testing, material degradation testing, and cell experiments, all performed in vitro. Results: Reinforcement of an 8 mm graft with the cords decreased dynamic elongation by 24%–76%, was positively related to dynamic stiffness, and increased the failure load by 44%–105%, during which LA-C showed maximum enhancement. Human ligament-derived fibroblasts showed good proliferation and vitality on each cord over 2 weeks and aligned themselves in the direction of the fibers, especially the UHMWPE portion. Discussion: This study supports the potential of partially degradable UHMWPE/PDO cords, particularly LA-C, for graft protection. Nervertheless, a higher proportion of biodegradable material results in lower stiffness, which may impair the protective and lead to mechanical instability during degradation.